First record of the moon crab Ashtoret lunaris (Forskål, 1775) from Syrian coasts - Ammar, I.; Arabia, I. (Mesopotamian Journal of Marine Sciences, 2021)
The number of aliens crustaceans is constantly increasing within the Syrian marine waters with the increasing of the interest in the marine biodiversity which allowed the discovery of many new species and various unrecorded species. The moon crab Ashtoret lunaris (Forskål, 1775) is recorded for the first time from the Syrian coast in the eastern Mediterranean. Two specimens of the Lessepsian crab A. lunaris were collected from Al-shokaifat area (at the north of Jableh). The specimens were collected by hand from the sandy shore on 7 August 2017.